Human Resource Development To Face The Digitalization Era - Ila Sakila; Asep Sugito (Pascasarjana STIE Miftahul Huda, 2025)
This research examines the urgency of human resource development (HR) in facing challenges and opportunities in the digitalization era. Digital transformation fundamentally changes the way organizations operate, so it demands adjustments to HR strategies to remain relevant and competitive. The main objective of this study is to analyze how organizations can adapt HR development programs, including training, recruitment, and talent management, to build the capabilities needed in the digital age. The research method used is a qualitative analysis of cases of digitalization implementation in various industrial sectors. The results show that digitalization requires not only technical skills (eg, data analysis and artificial intelligence), but also non-technical skills (soft skills) such as adaptability, critical thinking, and collaboration that are key to success.